Economic and social impacts of channeling investments towards development areas Low Humanity Case Study of Zalam Factories in Huraman Region - Kurdistan Region - Ahmed, Ammar Shihab; Qader, Ahmed Ismaeel (Journal of University of Human Development, 2016)
The investment is one of the most important channels used by the states for the promote economic development. Investment is a crucially important for many states in developing regions, thereby contributing directly and indirectly of providing the region's opportunities for new employment, and that leads to the development of skills of workers from the area, especially if the investment is based on modern technology as well as is influential in economic and social aspects directly. Furthermore, this activity creates a forehand and background linkages between economic sectors, as well as contribute increase in benefit indirectly. In this sense, the government's role is clear in directing and allocating those investments to the least developed areas in order to achieve economic and human development through follow distributional policies investments which is prepared by the Investment Authority. The empirical result shows that Project (Subject of the study) have a positive contribution to the national income and add-Value of gross product by (10.323) and (12.154) million dollars a year, respectively. This study also found that investment had a positive effect on Job creation and providing 119 jobs for local residents. Lastly, The Kurdistan region government should adopt a comprehensive plan and provide essential services to encourage local investors in the less developed regions and impose conditions on the investment in order to give job opportunities to the local residents, which are contributes to the economic and human development.